2016
DOI: 10.1016/j.jand.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Low-Fat Dietary Pattern Intervention and Health-Related Quality of Life: The Women’s Health Initiative Randomized Controlled Dietary Modification Trial

Abstract: Background Intensive dietary intervention programs may lead to benefits in vitality and other components of health quality. The Women’s Health Initiative (WHI) Dietary Modification (DM) intervention includes a large randomized controlled trial of an intensive intervention. Objective To evaluate whether the intervention is associated with improved health-related quality of life (HRQoL) subscales, overall self-reported health, depressive symptoms, cognitive functioning, and sleep quality. Design Randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…The findings of this meta-analysis reported a non-significant association between fruit and vegetable intake and breast cancer prognosis, probably because the consumption of fruits and vegetables may not be a strong dietary determinant of breast cancer mortality but has an indirect effect on breast cancer prognosis (41,42) . Many related articles regarding the association of fruit and vegetable intake with breast cancer prognosis mainly focus on the association between fruit and vegetable intake and weight change among breast cancer patients (43)(44)(45)(46)(47) . Thomson et al (48) indicated minimal short-term changes in body weight in response to a high-vegetable, low-fat diet in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this meta-analysis reported a non-significant association between fruit and vegetable intake and breast cancer prognosis, probably because the consumption of fruits and vegetables may not be a strong dietary determinant of breast cancer mortality but has an indirect effect on breast cancer prognosis (41,42) . Many related articles regarding the association of fruit and vegetable intake with breast cancer prognosis mainly focus on the association between fruit and vegetable intake and weight change among breast cancer patients (43)(44)(45)(46)(47) . Thomson et al (48) indicated minimal short-term changes in body weight in response to a high-vegetable, low-fat diet in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Studying QoL in healthy older adult populations may be especially important as it might have implications on our understanding of healthy ageing, and inform strategies for maintaining health in older years. The limited number of studies that have attempted to measure dietary patterns in relation to QoL have shown that adherence to healthy patterns may have beneficial effects on QoL in women [ 60 ] and in older adults [ 20 ]. The aim of this review was to evaluate evidence of the association between dietary patterns and QoL in older adults, with the intention of providing a better understanding of the potential for dietary patterns to improve QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Those who self-rated their diet quality as excellent, very good, or good were 3.1 times more likely to have a good or better (vs fair/poor) HRQOL, after adjusting for demographic and nutrition-related variables. Assaf et al (2016), Germain et al (2013), and Rasheed and Woods (2013) also investigated the relationship between diet and HRQOL though in different populations and with different diet quality and outcome measures. Rasheed and Woods (2013) conducted a systematic review and metaanalysis of studies examining nutrition and quality of life in older adults in both intervention and observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…This one global QOL item was on an 11-point scale, with 0= "As bad or worse than being dead" and 10= "Best quality of life." After one year, the SF-36 component scores for general health, physical functioning, and vitality significantly improved with the DM intervention, after adjusting for age, ethnicity, and weight, suggesting that dietary modification is associated with improved HRQOL (Assaf et al, 2016).…”
Section: Johansson Et Al 2009mentioning
confidence: 96%
See 1 more Smart Citation